Flexible robot configuration cell in manufacturing industry - Osman, Nor Suriyanti (UTeM, 2018)
Manufacturing configuration work is a very tedious process that relies on the way a system is determined and the experience of the person involved. This work is also based on the requirements set by the user. In this research work, the development of flexible approach for configuring robot work cell in manufacturing industry is presented. An articulated robot with six (6) degree of freedom (DOF) is taken as reference to represent the configuration layout because it is one of the most widely used robot in industries. The purpose of this research is to develop a new flexible approach for easy configuring robot work cell with minimal configuration time, less human or expert involvement and at little or no further investment. The different emerging strategies which focus on the configuration work has been highlighted and reviewed. In this work, a variant-shaped configuration concept with its mathematical equation for both workspace area, Aw and the manufacturing throughput time, MTT of each configuration layout have been developed. Later, a configuration framework with a set of rule selection has been created for further development of a graphical user interface (GUI) of flexible configuration model (FlexCoM). The developed FlexCoM would be used in determining the ideal robot work cell while satisfying the user requirements. Matlab and CATIA V5 software where it involves the CATIA VBA and macro tools were used in this research work. The developed FlexCoM has been tested and evaluated by three (3) different industries where the outcome of this research showed that the developed FlexCoM could assist design engineers in minimizing the configuration time, optimizing the human and expert involvement as well as capitalizing the available resource for investment while conducting robot work cell configuration work in the future. This research hopes that the industry will benefit from the outcome by having the ability to optimize the configuration system and to minimize the risk of investment.